RELAÇÕES ENTRE PERCEPÇÃO DE SUCESSO NA CARREIRA, BEM-ESTAR NO TRABALHO E DESEMPENHO - Costa, Antônio Roberto da (2012)
This thesis aims at analyzing the relationship between perception of career success, wellbeing at work and performance of teachers distance learning (DL). To this end, we conducted a survey using a self-report questionnaire to collect data with 128 teachers EaD a private higher institution located in the state of Rio de Janeiro. For a discussion of the results of the search and analysis of the data was used SPSS - Statistical Package for the Social Sciences, version 18.0 for Windows. We calculated averages, standard deviations, correlation coefficients (Pearson's r) and differences between means (Student t). The results indicate, through the responses to the instruments used, the teachers were successful in distance education teaching career as proportional to the other variables and it can be seen that teachers DL surveyed have high levels of well-being at work in their dimensions (job satisfaction, job involvement and affective organizational commitment) because they are satisfied in their jobs and very emotionally committed to the educational institution and finally, confirms the trend in the occurrence of significant levels of performance. Therefore, it is concluded that in relation to the perception of career success, well-being at work, and performance, the teachers studied are satisfied with their professional distance education, and the dimensions of wellness are preferred researchers because variables have positive and significant over other constructs of this research.